[Zbiór kart pocztowych z ks. Jerzym Popiełuszką] . Set of postcards with rev. Jerzy Popiełuszko (Polska, 1988)
2 postcards with single-sided, col. print on white paper, back divided into a notes and address field, with purple or green watermark and purple or blue stamp imprinted. 2 postcards, issued on the fourth anniversary of murder of rev. Jerzy Popiełuszko, contain imprinted watermarks and stamps. The stamps represent Popiełuszko with caption "God, honor, homeland". The watermarks with cross and hand in sign of victory, inform about the occasion, with date and caption "Chaplain of Solidarity".